Mycotic aortic aneurysm: a ticking time-bomb! - Bento, Rita; Rodrigues, Gonçalo; Alves, Gonçalo; Garcia, Rita; Pais, Fábio; Ferreira, Maria Emília (Angiologia e Cirurgia Vascular, 2023)
INTRODUCTION: Mycotic or primary infected aortic aneurysms comprise aproximately 1.3% of all aortic aneurysms and may be caused by septic emboli to the vasa vasorum, by haematogenous spread during bacteraemia or by direct extension of an adjacent infection leading to an infectious degeneration of the arterial wall and aneurysm formation. The objective of this report is to describe a clinical case of a complicated mycotic aortic aneurysm. CASE REPORT: A male, 69-year-old patient, with medical background of diabetes, hypertension and a bladder carcinoma (surgically ressected 5 years before, complicated at the time with an E.coli septicaemia), presented at the ER with generalised malaise, asthenia, anorexia, abdominal pain, diarrhea and fever, with 1 week of evolution. At admission, clinical examination revealed poor general condition, fever (39oC), noral blood pressure, and the abdominal examination showed no abnormalities. Laboratory results revealed an stable haemoglobin of 13 g/dL, leukocytosis (19850/UI) and neutrophilia (90%), an a C Reactive Protein of 350mg/dl. A Computed Tomography Angiography (CTA) revealed a 3,5 cm saccular juxtarenal AAA, with peri and intra- aortic gas, strongly suggestive of an mycotic AAA (MAA). Hospitalization was indicated and a septic and immunologic screening was perfomed. The patient started a broad-spectrum antibiotic with meropenem and vancomycin and clinical, laboratory and hemodynamic surveillance. Blood and urine cultures revealed a E.Coli infection, and directed antibiotic was started. After 10 days os hospitalization, the patient was haemodinamic stable, presented no fever or abdominal pain, however inflammatory parameters remained elevated, and a new CTA that showed a daunting increase of 4 cm of the AAA (7,5 cm) with signs of contained ruture. An emergency intervention was decided and the patient underwent an thoracophrenolaparotomy and aorto- aortic interposition with bovine pericardium patch. After 24h of surgery the patient died of septic shock. CONCLUSION: MAA is a rare and threatening disease with rapid progression and high mortality. Even with broad-spectrum antibiotic and rapid surgical response, the tragic outcome is often the unavoidable result